REGENERATION OF RURAL ARCHITECTURAL HERITAGE: CASE STUDY OF FIVE TRADITIONAL HOUSES IN SIRINIĆKA ŽUPA - Stefan Kovačević; Milena Krklješ; Saja Kosanović; Marija Stamenković; Alenka Fikfak; Janez Grom (Facta Universitatis. Series: Architecture and Civil Engineering)
The architectural legacy of Sirinićka Župa, located in the south part of the Republic of Serbia, at the foot of the Šar mountain, is best known by traditional houses. The uniqueness of the style of old Sirinić houses is attributed to the use of local materials and adaptation to local topography, climate and the morphology of settlements.